Diet and Genotype of an Aquatic Invertebrate Affect the Composition of Free-Living Microbial Communities - Macke, Emilie; Callens, Martijn; Massol, Francois; Vanoverberghe, Isabel; De Meester, Luc; Decaestecker, Ellen (Frontiers in Microbiology, 2020)
In spite of the growing interest in the role of the gut microbiome in host physiology and health, the mechanisms governing its assembly and its effects on the environment are poorly understood. In this article, we show that the host genotype and the gut microbiome of Daphnia influence the community structure of the surrounding bacterioplankton. When Daphnia genotypes were placed in an identical environment, both the gut microbiome and the bacterioplankton showed a genotype and diet-dependent taxonomic composition. Overall, the gut microbiome strongly differed from the bacterioplankton in taxonomic composition and was characterized by a lower α-diversity, suggesting a selective rejecting of bacteria from the regional species pool. In a microbiome transplant experiment, the assembly of both the gut microbiome and the bacterioplankton was strongly affected by the host genotype and the inoculum to which germ-free Daphnia were exposed. The combination of these results suggests a strong interaction between the host genotype, its gut microbiome and free-living microbial communities. Currently, it is generally assumed that an animal's diet has a strong effect on the animal's gut microbiome, but only a negligible (if any) effect on the surrounding environment. However, our results indicate that the diet/microbiome inocula have a small effect on the gut community and a large effect on the community in the surrounding environment. This structuring genotype x microbiome x environment effect is an essential prerequisite that could indicate that microbiomes play an important role in eco-evolutionary processes.